Case Report of Faded Bedtime Intervention on Delayed Sleep-Onset and Sleep Duration in an Adolescent with Autism Spectrum Disorder. Issue 2 (3rd April 2021) - Luiselli, James K.; Harper, Jill M.; Murphy, Kerrianne J.; Leach, Matthew; Luke, Katherine
Abstract: Delayed sleep-onset is a common problem among children and youth with intellectual and developmental disabilities. This case report describes the effects of a faded bedtime intervention on delayed sleep-onset and sleep duration in an adolescent student with autism spectrum disorder (ASD) at a residential-care setting. Faded bedtime consisted of putting him to bed later in the evening following an extended pre-bedtime routine that was based on his average time to sleep-onset recorded during a pre-intervention phase. Faded bedtime was associated with the student falling asleep more rapidly and sleeping longer each night. These outcomes improved further at a two-month follow-up assessment. Compared to previous research, the results suggest that faded bedtime can be effective beyond hospital and family-home settings, when implemented with a fixed (non-adjusting) daily schedule, and without additional intervention procedures.